Apuntes sobre el reconocimiento del derecho a la educación superior a las mujeres - Vidal Cabeza de Tarazona, Gisela Hortencia (2012)
The present talks about the difficultAccess to the right to higher educationof Peruvian women in the XIX century,the international legal instrumentsissued guaranteeing its right to Accessto university studies, as well as thecurrent situation in some countries(mostly muslim religion) where it is stilldenied to women the opportunity tostudy at a university.